Financial Development and Economic Growth: The Case of Nigeria - Eyo, Kufre Dominic (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2012)
ABSTRACT: The link between the financial development and economic growth is a widely investigated area in economic literature. Most cross-country studies established a positive relationship between financial development and economic growth pioneered by McKinnon and Shaw (1973). However, empirical research in low income countries, especially in most African and Latin American countries did not support the positive link hypotheses despite the liberalization of their financial markets. This raised questions on the strength of the relationship as large capital flows encouraged by financial liberalization made the countries more prone to crises exerting even negative impacts on such economies. This research seeks to explore any possible relationship between financial development and economic growth in Nigeria within a vector autoregressive (VAR) framework and also study the direction of causation. Following Demirguc-Kunt and Levine (1979) different channels of financial development are studied by distinguishing between the banking and the stock market development. The empirical results indicate that the banking sector plays an important role in the long-run contributing positively to economic growth while the stock market exerts no impact to long-run economic growth. Based on the bivariate models there is strong evidence of a unidirectional Granger-causality relationship from money supply to economic growth and a weak support for other financial development variables. Considering higher dimensional system, there is strong evidence of a feedback effect among economic growth and financial development variables over the sample period. Keywords: Financial Development, Economics Growth and Nigeria. ………………………………………………………………………………………………………………………… ÖZ: Ekonomik büyüme ve finansal gelişme arasındaki ilişki ekonomi literatüründe sıkça irdelenen konular arsında yer almaktadır.Çoğu ülkelerarası çalışmalar, Mckinnon ve Shaw’ın (1973) öncülüğünü yaptığı finasal gelişme ile ekonomik büyüme arasındaki positif ilişkiyi desteklemiştir. Ancak, düşük gelirli ülkeler, özellikle Afrika ve Latin Amerika için yapılan ampirik çalışmalar finansal serbestleşmeye rağmen pozitif ilişki hipotezini desteklememiştir. Bunun sonucunda, ekonomik büyüme ve finansal gelişme arasındaki ilişkinin niteliği hakkında kuşkular uyanmıştır. Bu çalışmada, 1961-2010 yılları arasında vektor otoregresif (VAR) yaklaşımı kullanılarak Nijerya’daki ekonomik büyüme ile finansal gelişme arasındaki ilişki incelenmektedir. Demirguc-Kunt and Levine’in (1979) önerileri çerçevesinde bu ilişkide bankacılık ve hisse senetleri piyasalarındaki gelişmelerin etkileri ayrıca dikkate alınmaktadır. Çalışmanın ampirik bulgularına göre, ekonomik büyümede bankacılık sektörünün önemli bir rol oynadığı, hisse senetleri piyasasının katkısının olmadığı görülmüştür. Granger nedensellik test sonuçları ise para arzının tek taraflı anlamlı olduğu diğer finansal değişkenlerin ekonomik büyüme ile Granger nedensellik ilişkisinin zayıf olduğu bulunmuştur. Değişkenlerin birbirleriyle ilişkilerini dikkate alan tüm sistem içindeki Granger nedensellik test sonuclari ise ilişkinin heriki yönde ve tüm değişkenler arasında oldukça anlamlı olduğunu göstermiştir. Anahtar kelimeler: finansal gelişme, Ekonomik Büyüme ve Nijerya.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2012. Supervisor: Assoc. Prof. Dr. Gülcay Tuna Payaslıoğlu.
Keywords: Economics; Economic Conditions - Nigeria; Financial Development Economic Growth and Nigeria